2023
DOI: 10.1021/acscatal.3c02262
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Nonheme Iron Enzyme NapI React through l-Arginine Desaturation Rather Than Hydroxylation? A Quantum Mechanics/Molecular Mechanics Study

Hafiz Saqib Ali,
Jim Warwicker,
Sam P. de Visser

Abstract: The naphthyridinomycin biosynthesis enzyme NapI selectively performs the desaturation of a free L-arginine amino acid at the C 4 −C 5 bond as part of its antibiotic biosynthesis reaction. This is an unusual reaction triggered by a nonheme iron dioxygenase as most L-Arg activating nonheme iron enzymes cause substrate hydroxylation at an aliphatic C−H bond; hence, this reaction has great potential in biotechnology for the efficient synthesis of drug and fragrance molecules. However, desaturation reactions in che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…By contrast, in the naphthyridinomycin biosynthesis enzyme NapI, the dipole is along the substrate backbone and appear not to influence the C−H bond strengths in the substrate. 117 As a consequence, in NapI, the weakest C−H bond in the gas phase is activated by the protein, whereas in VioC, one of the stronger bonds is activated instead. The dipole moment in model C is also perpendicular to the aromatic ring of Tyr 233 and hence is likely to stabilize a radical center on this group and trigger an electron transfer from Tyr 233 to iron(IV)-oxo and a simultaneous proton transfer from Tyr 233 to Asp 179 .…”
Section: ■ Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, in the naphthyridinomycin biosynthesis enzyme NapI, the dipole is along the substrate backbone and appear not to influence the C−H bond strengths in the substrate. 117 As a consequence, in NapI, the weakest C−H bond in the gas phase is activated by the protein, whereas in VioC, one of the stronger bonds is activated instead. The dipole moment in model C is also perpendicular to the aromatic ring of Tyr 233 and hence is likely to stabilize a radical center on this group and trigger an electron transfer from Tyr 233 to iron(IV)-oxo and a simultaneous proton transfer from Tyr 233 to Asp 179 .…”
Section: ■ Discussionmentioning
confidence: 89%
“…In VioC, the dipole moment therefore guides the reaction selectivity and triggers a lesser thermodynamic favorable pathway. By contrast, in the naphthyridinomycin biosynthesis enzyme NapI, the dipole is along the substrate backbone and appear not to influence the C–H bond strengths in the substrate . As a consequence, in NapI, the weakest C–H bond in the gas phase is activated by the protein, whereas in VioC, one of the stronger bonds is activated instead.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, single-point calculations at the UB3LYP-GD3/BS2 level of theory were run in Gaussian with an electric field located along the molecular x , y , or z axis, with magnitudes ranging from −200 to +200 au, and the results are shown in Figure . These electric-field perturbations were used previously in our group and shown to influence charge distributions in complexes and bifurcation patterns in chemical catalysis. , In particular, recent work showed that charged groups in proteins can influence the strength of the C–H bonds in substrates and direct a reaction selectivity to a specific bond in a substrate. , Thus, an electric-field perturbation has a major effect on the thermodynamics for proton transfer and the reaction energy. To be specific, an electric-field effect along the negative z axis is along the proton-transfer axis and makes the first proton-transfer step more exergonic, while a field in the opposite direction makes the reaction more endergonic, i.e., less likely.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, studies on NvfI, TqaL, AspE, KabC, PIsnB, and PvcB have reported such findings. Since the feasibility of single ET between the substrate radical and Fe III –OH [in pathway (c)] is debatable from the thermodynamic perspective, we should still be cautious regarding the detailed steps in certain cases. The uncertainty may be attributed to factors such as the redox potential of Fe III –OH, the ET barrier between the substrate radical and cation intermediate, the incompatibility of an unstable cation intermediate in the enzyme binding pocket, and the structural properties of substrates.…”
Section: Discussionmentioning
confidence: 99%